Geographic distribution of Trypanosoma cruzi genotypes detected in chronic infected people from Argentina. Association with climatic variables and clinical manifestations of Chagas disease - Bizai, María L.; Romina, Peralta; Antonela, Simonetto; Olivera, Lorena V.; Arias, Evelyn E.; Josefina, Dalla Costa; Silvia, Manattini; Walter, Sione; Diana, Fabbro; Cristina, Diez (Infection, genetics and evolution, 2020)
Chronic Chagas disease affects large number of people in Latin America where it remains one of the biggest public health problems. Trypanosoma cruzi is genetically divided into seven discrete typing units (DTUs), TcI-TcVI and Tcbat, and exhibits differential distribution across vectors, host and transmission cycles. Clinical manifestations (cardiac, digestive and / or neurological) vary according to the geographical region; and the DTUs more frequently found in any of the chronic form of the disease, indeterminate or clinical, are TcI, TcII, TcV and TcVI. However, why they have a particular geographical distribution and how they affect the development of Chagas disease is still unknown. In this study, we assessed the geographic distribution of T. cruzi genotypes detected in chronic infected people from 57 localities of endemic regions of Argentina and analyzed their association with climatic variables. The prevalent DTUs detected in the whole population were TcV (47.4%) and TcVI (66.0%). TcI and TcII were identified in 5.2% each. All DTUs were detected in single and mixed infections (78.4% and 21.6%, respectively). TcV was found in infected people from localities with significantly higher average annual temperature, seasonal temperature and annual temperature range than those infected with TcVI. When we evaluated the association of DTUs with clinical manifestations of Chagas disease, the probability of finding TcVI in subjects with chronic Chagas cardiomyopathy (CCC) was higher than other DTUs, but without reaching statistical significance. Moreover, the probability of finding TcV in those who have not developed the disease after 20 years of infection was significantly higher than in CCC, either if it was present as unique DTU (reciprocal OR=4.95 95%CI: 1.42 to 17.27) (p=0.0117) or if it was also part of mixed infections (reciprocal OR=3.375; 95%CI: 1.227 to 9.276) (p=0.0264). There was no difference in the distribution of TcI between asymptomatic people and those with clinical manifestations, while TcII appeared more frequently in CCC cases, but without statiscal significance. •The prevalent DTUs detected in the whole population were TcV and TcVI, whether in single and mixed infections.•People infected with TcV came from localities with higher average temperatures than those infected with TcVI.•The probability of finding TcV in those people who remained asymptomatic for more than 20 years was higher than in CCC.